How a centralised approach to learning design influences students: a mixed methods study. Issue 4 (7th June 2021) - Bearman, Margaret; Lambert, Sarah; O'Donnell, Marcus
ABSTRACT: In online education, learning design has a significant role in mediating student experience. Centralised approaches to learning design provide students with a coherent teaching approach across online units but little is known about their impact on the student. Understanding the influence of these overarching learning design features may be a significant piece in improving online coursework at scale. In the context of this study, a central learning design team created learning design patterns within the FutureLearn platform, which teaching teams subsequently used to develop student-facing unit learning materials. A mixed methods investigation sought to understand how the learning design patterns influenced (1) student outcomes and (2) student experiences across units. We collected enrolment and institutional satisfaction data, conducted a qualitative survey (39 respondents) and interviewed 14 students. Quantitative analysis suggested that the approach may have improved retention although satisfaction appeared unchanged. The qualitative data indicated that, in general, learning design elements such as social media style discussion enable and constrain the student learning experience simultaneously. For example, stepwise approaches to learning help orient and guide students but may also be overly atomistic. This suggests both software choice and learning design patterns can have a mixed effect on the student experience. Course teams may wish to consider how teaching materials can maximise the benefits and mitigate against the foreseeable drawbacks of centralised learning designs and software platforms.